Pengaruh Pelaksanaan Senam Program Pengelolaan Penyakit Kronis (Prolanis) terhadap Kardiorespirasi pada Lansia di Desa Baini dan Konggamea wilayah Kerja Puskesmas Sampara Kabupaten Konawe - Saputra, Ardan; Lestari, Sari Ari (Jurnal Gizi Ilmiah, 2017)
The number of elderly in the Sampara Public Health Center Working Area, Konawe Regency in 2015 amounted to 215 people in 15 villages, with the highest number of elderly in Baini and Konggamea villages amounting to 21 people, the problem of Elderly exercise which is carried out once a week by the Puskesmas is PROLANIS gymnastics aims to maintain cardiorespiratory function but relatively few follow the elderly. The purpose of the study was to determine the effect of implementing PROLANIS exercise on Cardiorespiratory in the Elderly in Baini and Konggamea Villages in 2016. This research method is an experiment with a pre-experimental design in the form of pre-test and post-test designs. The population of all elderly in two villages within the working area of ​​the Sampara Health Center, namely Baini and Konggamea, amounted to 21 people. Samples were taken using purposive sampling technique amounted to 17. Mc Nemar analysis. Cardiorespiratory research results in the elderly before the exercise program were mostly normal with pulse, breathing and blood pressure all normal, while walking for 12 minutes was normal for 10 people (58.8%) and 7 people were not normal (41.2%). Cardiorespiration in the elderly after exercise was mostly normal with pulse, respiration and blood pressure all normal, while walking for 12 minutes was normal for 16 people (94.1%) and 1 person was abnormal (5.9%). There is an effect of implementing PROLANIS exercise on Cardiorespiratory in the Elderly in Baini and Konggamea Villages, Sampara District, Konawe Regency in 2016. Suggestions for the elderly to take advantage of elderly exercise as a means of cardiorespiratory fitness treatment